Pengenalan Pupuk PSB Oleh Mahasiswa KKN Universitas Sebelas Maret Di Desa Belor, Grobogan - Sudibya; Shinta Novia Sukma; Rio Abei Santoso; Ory Febriayani; Salsabila Ainun Nisa; Putri Salsabilla; Raihan Rafif Kautsar Priyanto; Rina Wahyu Ramadhani; Rizky Nugraha Ramadhan; Richardo Novtanta Farizaldi (KREASI : Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2022)
In the implementation of KKN Tematik UNS, there are several aspects that will be implemented, i.e., education, social environment, and health. One of the working plans is the Socialization and Demonstration of Making PSB (Photosynthetic bacteria) Fertilizer. This socialization and demonstration event aims to introduce PSB to the community and to reduce the use of chemical fertilizers. The method used is to do a situation analysis, literature review, and implementation of demonstration socialization. PSB are autotrophic bacteria, which can convert inorganic substances into organic and make their own food with the help of sunlight as food through the process of photosynthesis. In-plant growth and development, PSB has a role and benefit to help nitrogen needs for all types of plants, adding hydrogen sulfide gas in the soil structure from the decomposition of organic matter, accelerating plant growth, enriching amino acids, nucleic acids, physiologically active compounds, and polysaccharides. In the soil, improves the quality and taste of the fruit of plants, strengthens plant roots, strengthens plants from various pests and diseases, makes the bark of plant stems stronger and more resistant to insects.